2020
DOI: 10.3390/cells9051304
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Features of Human Perinatal Stem Cells Redefine Their Stemness Potential

Abstract: Human perinatal stem cells (SCs) can be isolated from fetal annexes without ethical or safety limitations. They are generally considered multipotent; nevertheless, their biological characteristics are still not fully understood. The aim of this study was to investigate the pluripotency potential of human perinatal SCs as compared to human induced pluripotent stem cells (hiPSCs). Despite the low expression of the pluripotent factors NANOG, OCT4, SOX2, and C-KIT in perinatal SC, we observed minor differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…In contrast to other parts of the placenta, human amniotic epithelial stem cells are derived from the pluripotent epiblast at around 8 days after fertilization, which happens prior to gastrulation; thus, it is reasonable to hypothesize that a certain proportion of hAESCs may retain the plasticity of pregastrulation embryo cells. Indeed, the latest research revealed that the pluripotent factors NANOG, OCT4, and SOX2 are not fully silenced in hAESCs, as their promoters are only partially methylated, displaying a similar epigenetic profile compared with hiPSCs, and their downregulation is regulated at the post-transcriptional levels by specific miRNAs [ 36 ]. Meanwhile, Miki et al reported that most hAESCs express some ESC-associated pluripotent markers, such as OCT-4, NANOG, SSEA-3, SSEA-4, TRA-1-60, and TRA-1-80, in the early stage [ 16 ].…”
Section: The Plasticity Of Human Amniotic Epithelial Stem Cells Asmentioning
confidence: 99%
“…In contrast to other parts of the placenta, human amniotic epithelial stem cells are derived from the pluripotent epiblast at around 8 days after fertilization, which happens prior to gastrulation; thus, it is reasonable to hypothesize that a certain proportion of hAESCs may retain the plasticity of pregastrulation embryo cells. Indeed, the latest research revealed that the pluripotent factors NANOG, OCT4, and SOX2 are not fully silenced in hAESCs, as their promoters are only partially methylated, displaying a similar epigenetic profile compared with hiPSCs, and their downregulation is regulated at the post-transcriptional levels by specific miRNAs [ 36 ]. Meanwhile, Miki et al reported that most hAESCs express some ESC-associated pluripotent markers, such as OCT-4, NANOG, SSEA-3, SSEA-4, TRA-1-60, and TRA-1-80, in the early stage [ 16 ].…”
Section: The Plasticity Of Human Amniotic Epithelial Stem Cells Asmentioning
confidence: 99%
“…Currently, the only cells with proven promising results regarding cardiogenic potential are hiPSCs. The possibility to obtain functionally mature CMs from patient-specific hiPSCs is a big challenge for clinical use in tailored cell therapy [ 5 , 29 , 30 , 31 , 32 , 33 ], with their epigenetic instability still considered an unsolved issue [ 10 ]. The recent discovery that Cardiopoietic AF could circumvent any ethical and safety concerns and provide effective cell replacement therapy for cardiac diseases, particularly in congenital heart defect repair applications, [ 2 , 34 , 35 ] opened the door to a new scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained with human induced pluripotent stem cells (hiPSCs) showed that these cells can efficiently differentiate into patient-specific beating CMs in vitro [ 6 , 7 , 8 ], but their clinical use must be tempered due to their tumorigenic potential [ 5 ]. Recently, we proposed an alternative and safer stem cell source, demonstrating that human amniotic fluid cells that express the multipotency markers SSEA4, OCT4, and CD90 ( Cardiopoietic AF cells), if properly cultured on Matrigel ® in presence of differentiative factors, can give rise to a morphologically homogeneous population of CMs that, similar to hiPSC-derived CMs, express cardiac-specific proteins and may contract spontaneously [ 2 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like all mesenchymal stem cells, hFM-MSCs are generally considered multipotent. However, previous data from our lab evidenced that the epigenetic profile of hFM-MSCs did not completely differ from that of hiPSCs [11]. To better characterize the stemness of hFM-MSCs, we analyzed the transcriptional profiles of embryonic markers known to be abundantly and uniquely expressed in pluripotent stem cells, such as hESC and hiPSCs.…”
Section: Hfm-mscs Exhibit Some Molecular and Biological Characteristimentioning
confidence: 98%
“…Generally, hFM-MSCs are considered multipotent stem cells, able to differentiate into mesenchymal lineages, such as chondrogenic, adipogenic, and osteogenic progenies [10]. Regardless, their differentiative potential and their real position in the stemness hierarchy are not completely elucidated [11]: it has been reported, indeed, that hFM-MSCs expressed some pluripotent markers and that they share with hiPSCs the methylation profile of some stem genes.…”
Section: Introductionmentioning
confidence: 99%